O fazer a feira: a feira noturna da agricultura familiar de Araraquara-SP como espaço de reprodução social e econômica - Vieira, Camila Benjamim [UNESP] (2017)
Part of a city project called "Business of the Field", the family farming Night Fair in Araraquara-SP, takes place every thursday afternoon since July 2014 in the courtyard of the city Railway station. The fair (a kind of marketplace) has about 36 farmers, including tents of fruits and vegetables, food and handicrafts, with approximately 800 consumers per fair. It’s a space physically defined, but endowed with an amplitude of social relations that crosses it’s borders. This amplitude becomes more complex when we add specificities of the fair in question, as most of its marketers are settled family farmers, a characteristic that attributes particular meanings to these marketers, due to the inseparable relationship of home / work / family. This research’s objective is to analyze the family farming Night Fair in Araraquara-SP as space of social and economic reproduction of the fairgrounds. To do that, the theoretical methodological clipping used was a bibliographical revision about fairs and family farming in Brazil, with ten intentional interviews and eight months of fieldwork, supported by Pierre Bourdieu's reflective sociology, coupled with economic sociology and rural sociology.